The Never‐Ending Road Towards the CEAS: Utopia, Teleology, and Depoliticisation in EU Asylum Policies - Vianelli, Lorenzo (2022)
This article explores the temporal dimension of the Common European Asylum System (CEAS) by exposing its teleological character and the effects of the latter on the governance of asylum in the European Union. Drawing on EU policy documents, the article shows how the CEAS has been presented since its inception as a teleology, that is, a process that is inexorably unfolding towards a specific outcome to be reached in an indefinite time in the future. The outcome consists in the establishment of a common area of protection constituted by a level playing field in which asylum seekers and beneficiaries of international protection will be treated alike regardless of the place of residence. Such a teleological narrative informing the CEAS paves the way to overly optimistic expectations on the possibilities of implementation, which in turn result in an overestimation of the potential of harmonisation. By discussing the limitations of harmonisation in relation to the reception of asylum seekers, this article calls into question the possibility of a homogeneous area of protection where equivalent conditions are offered to all asylum seekers across the EU. Such a homogeneous space is utopian because harmonisation does not aim to eradicate differences but rather to mitigate them, thus tolerating diverse arrangements. The article, therefore, argues that the level playing field projected by the CEAS constitutes a promise that has two key effects: First, it depoliticises the CEAS itself by framing problems as technical issues, requiring technical solutions; second, it paves the way to further EU intervention in this field.